1981
DOI: 10.1289/ehp.8137117
|View full text |Cite
|
Sign up to set email alerts
|

Bioassaying for ozone with pollen systems.

Abstract: Sensitivity to ozone of pollen germinating in vitro is closely correlated with ozone sensitivity of the pollen parent. Ozone-sensitive and tolerant pollen populations have been identified in tobacco, petunia, and tomato cultivars. The rate of tube elongation can be reversibly slowed or stopped by exposure to low concentrations of ozone. Tube growth rates in the presence of a range of ozone dosages, of pollen populations exhibiting differing ozone sensitivity can be measured and different growth rates can be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…For example, when artificially polluting Ambrosia artemisiifolia pollen with O 3 , Pasqualini et al could clearly show that the viability was rather low on 7-day O 3 − fumigated pollen (39%) compared to the control sample (56%) [ 157 ]. On pollen of cultivated plants (tomato, tobacco, and petunia), Feder showed that the pollen viability can be reversibly slowed or stopped by exposure to low concentrations of O 3 [ 158 ]. O 3 effect can also be observed in Lolium perenne pollen.…”
Section: Effects Of Pollutants On Pollen Grains and Pollen Contentmentioning
confidence: 99%
“…For example, when artificially polluting Ambrosia artemisiifolia pollen with O 3 , Pasqualini et al could clearly show that the viability was rather low on 7-day O 3 − fumigated pollen (39%) compared to the control sample (56%) [ 157 ]. On pollen of cultivated plants (tomato, tobacco, and petunia), Feder showed that the pollen viability can be reversibly slowed or stopped by exposure to low concentrations of O 3 [ 158 ]. O 3 effect can also be observed in Lolium perenne pollen.…”
Section: Effects Of Pollutants On Pollen Grains and Pollen Contentmentioning
confidence: 99%
“…Ozone entry into the apoplastic space in reproductive structures leads to ROS production, which can lead to changes in the stigmatal surface and cell membranes (Feder & Shrier, ). The ROS also affect the ability of pollen to germinate on the stigmatal surface (Mumford et al ., ; Harrison & Feder, ; Krause et al ., ; Feder, ; Feder et al ., ; Benoit et al ., ; Hormaza et al ., ). Moreover, ROS‐mediated changes in the cellular redox environment can potentially lead to changes in pollen tube growth and guidance, which is critical for fertilization of the embryo.…”
Section: Introductionmentioning
confidence: 99%
“…Such tests are especially important because metal hyperaccumulators occur in many systems across the globe and are increasingly used in phytoremediation (Sarma, 2011) where they may transfer pollen to native species if shared pollinators are not deterred by metals (Meindl and Ashman, 2014; Hladun et al, 2013). Moreover, because gametophytes and sporophytes share many genes and have similar responses to environmental stressors (such as temperature and salinity) (e.g., Herrero and Johnson, 1980; Feder, 1981; Rutley and Twell, 2015) this study opens the window on an underappreciated possibility that chemical mediation of sporophyte interactions also plays a role in pollen interactions on the stigma.…”
Section: Discussionmentioning
confidence: 95%